Dampak Penyertaan Saham oleh Bank terhadap Nilai Perusahaan Induk: Studi Empiris pada Bank Tercatat di BEI - Aini Feriska Sumandya; David Tan; Della Aprianingrum; Silvy Pricilia Fernanda; Siti Aisyah Rukmana (Politeknik Raflesia Press, 2025)
This study aims to analyze the impact of equity participation by banks on the value of the parent company. Equity participation is a long-term investment strategy that can affect the value of the company through diversification, business synergy, and increasing non-interest income. This study uses a quantitative approach with secondary data from the financial statements of banks listed on the Indonesia Stock Exchange (IDX) for the period 2018–2023. The analysis was carried out using multiple linear regression to test the effect of equity participation on the value of the company as proxied by Tobin's Q. The results of the study indicate that equity participation by banks has a significant positive effect on the value of the parent company. The implications of this finding indicate that equity participation can be a strategy to increase company value if managed properly.